2009
DOI: 10.2135/cropsci2007.12.0677
|View full text |Cite
|
Sign up to set email alerts
|

Inbred‐Progeny Selection Is Predicted to Be Inferior to Half‐Sib Selection for Three Maize Populations

Abstract: Historically, inbred progeny selection has been promoted as an effective means of improving both inbred and outbred performance, and in some cases as being superior to other methods. Advances in theory and new estimates of genotypic covariance components have allowed us to make better predictions of gain from inbred progeny selection than previously available. We developed predicted gain equations using a full model, based on new theory and estimates, and a reduced model, which contained only the additive gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…They concluded that the selection method involving inbred progenies was responsible for the superior gains from selection in BS11 compared with other selection methods. Contrary to theoretical arguments that recurrent selection involving inbred progenies is superior to mass selection and the half-sib recurrent selection methods, it has been demonstrated empirically that S 1 or S 2 family selection is not always superior (Coors, 1999;Wardyn et al, 2009;Edwards, 2010). For example, Wardyn et al (2009) demonstrated that predicted responses to S 1 or S 2 family selection did not show any advantages over half-sib methods in three maize populations.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…They concluded that the selection method involving inbred progenies was responsible for the superior gains from selection in BS11 compared with other selection methods. Contrary to theoretical arguments that recurrent selection involving inbred progenies is superior to mass selection and the half-sib recurrent selection methods, it has been demonstrated empirically that S 1 or S 2 family selection is not always superior (Coors, 1999;Wardyn et al, 2009;Edwards, 2010). For example, Wardyn et al (2009) demonstrated that predicted responses to S 1 or S 2 family selection did not show any advantages over half-sib methods in three maize populations.…”
mentioning
confidence: 73%
“…They concluded that dominance genetic variance was equally important and needed to be considered in future selection programs. Contrary to theoretical arguments that recurrent selection involving inbred progenies is superior to mass selection and the half-sib recurrent selection methods, it has been demonstrated empirically that S 1 or S 2 family selection is not always superior (Coors, 1999;Wardyn et al, 2009;Edwards, 2010). In the absence of over dominance, the S 1 or S 2 family selection method is superior to other population improvement methods (Lamkey, 1992).…”
Section: Genetic Variances and Heritabilities Of Traits Of An Early Ymentioning
confidence: 95%
See 2 more Smart Citations
“…Seleksi genotipe jagung dapat dilakukan berdasarkan produksi dan karakter lainnya (Wardyn et al, 2009). Tabel 4 menunjukkan sepuluh genotipe terbaik generasi S 1 berdasarkan produksi.…”
Section: Seleksi Pada Berbagai Karakter Terhadap Genotipe Uji Jagung unclassified